Wheat Variety Response to Seed Cleaning Method and Pesticide Seed Treatment Following a Growing Season with Severe Infestation of Fusarium Head Blight - R. Lollato; R. Maeoka; B. R. Jaenisch; A. de Oliveira Silva (Kansas Agricultural Experiment Station Research Reports, 2017)
Fusarium head blight (scab) is a common concern in eastern and central Kansas. Wheat seed quality might be compromised following a growing season with severe infestation of scab. Our objectives were to evaluate the effects of variety, seed cleaning method, and seed treatment, on wheat stand establishment and yield following a growing season where scab was severe. A trial was established during the 2015-16 growing season using seed harvested from the 2014-15 growing season, which was characterized by severe infestation of scab. Three commonly grown wheat varieties with differing levels of scab resistance (Everest, SY Wolf, and WB Grainfield) were submitted to three different seed cleaning methods (unclean, air screened, or top-gravity table) and two different pesticide seed treatments (no seed treatment versus Gaucho XT fungicide and insecticide). Plots were 30 feet long by 5.6 feet wide and sown at 1.2 million seeds per acre. Seed cleaning method affected wheat seed size, with top-gravity table resulting in larger seed size, approximately 3,000 fewer seeds per pound compared to unclean seed. Seed cleaning method also increased stand establishment from 10.4 emerged plants per row foot resulting from the unclean seed to 11.9 emerged plants per row foot resulting from the top-gravity table. Notwithstanding, there was no effect of variety or seed treatment on stand establishment. Grain yield, on the other hand, was increased from 55.6 to 61.3 bushels per acre in response to seed treatment and was significantly different among varieties. The variety WB Grainfield yielded 68.4 bushels per acre, which was statistically greater than the 53 bushels per acre achieved by both Everest and SY Wolf. There was no effect of seed cleaning method on grain yield.
Keywords: Wheat; head blight; scab; Fusarium; seed treatment; seed cleaning